1999
DOI: 10.1084/jem.189.7.1053
|View full text |Cite
|
Sign up to set email alerts
|

In Autoimmune Diabetes the Transition from Benign to Pernicious Insulitis Requires an Islet Cell Response to Tumor Necrosis Factor α

Abstract: The islet-infiltrating and disease-causing leukocytes that are a hallmark of insulin-dependent diabetes mellitus produce and respond to a set of cytokine molecules. Of these, interleukin 1β, tumor necrosis factor (TNF)-α, and interferon (IFN)-γ are perhaps the most important. However, as pleiotropic molecules, they can impact the path leading to β cell apoptosis and diabetes at multiple points. To understand how these cytokines influence both the formative and effector phases of insulitis, it is critical to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
120
1
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 62 publications
8
120
1
1
Order By: Relevance
“…However, the in vivo role of the cytokine in diabetes development has not yet been fully elucidated. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Our IFN-␥/TNF-␣ synergism model nicely explains why transgenic expression of TNF-␣ alone could not induce diabetes in some of the previous studies in which pancreatic expression of TNF-␣ alone did not accelerate diabetes development (21).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…However, the in vivo role of the cytokine in diabetes development has not yet been fully elucidated. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Our IFN-␥/TNF-␣ synergism model nicely explains why transgenic expression of TNF-␣ alone could not induce diabetes in some of the previous studies in which pancreatic expression of TNF-␣ alone did not accelerate diabetes development (21).…”
Section: Discussionsupporting
confidence: 57%
“…The role of TNF-␣ as an effector has been extremely ambiguous. Its diabetogenic role was suggested in some studies (13)(14)(15)(16)(17)(18), whereas opposite effects were reported in other studies (19,20). Neonatal islet-specific expression of TNF-␣ promoted diabetes by enhancing the presentation of islet Ags (16,17).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Our evidence presented in this report supports the action of macrophage-mediated islet ␤-cell death because of several reasons: electron micrographs of islet infiltrates demonstrated the presence of macrophages adjoining dying ␤ cells, and importantly, islets from mice deficient in inducible nitricoxide synthase were efficiently destroyed by BDC T cells. 15 Moreover, NOD mice that harbor a mutation in the inducible nitric-oxide synthase gene developed diabetes with the same kinetics and penetrance as wild-type NOD mice (personal communication with John Mudgett, Merck Inc., San Diego, CA). Further, cytotoxicity assays as shown in Figure 8 (and by others 44 -46 ) needed the presence of macrophages.…”
Section: Macrophages Kill ␤ Cells In T1dm 2143mentioning
confidence: 99%
“…It is important to note that in our model a role for Fas/FasL in mediating ␤-cell death is minor because Fas-deficient islets are efficiently destroyed by activated BDC T cells. 15 Finally, are activated macrophages also a participant in the natural disease? Certainly activated macrophages are a component of the infiltrate at the aggressive phase of the disease, that is, at the time of diabetes development.…”
Section: Macrophages Kill ␤ Cells In T1dm 2143mentioning
confidence: 99%